Growth and Management of Repaired Complete Tracheal Rings after Slide Tracheoplasty. (9th April 2019) - Wilcox, Lyndy J.; Schweiger, Claudia; Hart, Catherine K.; de Alarcon, Alessandro; Peddireddy, Nithin S.; Rutter, Michael J.
Abstract : Objective: This study documents the growth and course of repaired complete tracheal rings over time after slide tracheoplasty. Study Design: Case series with review. Setting: Tertiary pediatric academic medical center. Subjects/Methods: Medical records of pediatric patients with confirmed tracheal rings on bronchoscopy who underwent slide tracheoplasty between January 2001 and December 2015 were reviewed. Patients who had operative notes documenting tracheal sizing over time were included. Exclusion criteria included tracheal stenosis not caused by complete tracheal rings, surgical repair prior to presentation at our institution, or lack of adequate sizing information. The postoperative follow‐up was examined and airway growth over time documented. Results: Of 197 slide tracheoplasties performed during the study time period, 139 were for complete tracheal rings, and 40 of those children met inclusion criteria. The median age at time of surgery was 7 months, and the median initial airway size was 3.9 mm (n = 34). The median growth postoperatively was 1.9 mm over a median follow‐up period of 57 months (0.42 mm/year), which is similar to growth rates of unrepaired complete tracheal rings ( P =. 53). Children underwent a median of 10 postoperative endoscopies, with time between endoscopies increasing further out from surgery. The most commonly performed adjunctive procedure was balloon dilation. Conclusions: This is the first study documenting continued growth of repaired complete tracheal rings after slide tracheoplasty. Postoperative endoscopic surveillance ensures adequate growth. Intervals between airway endoscopies can be increased as the child gets older, as the airway increases in size, and as long as symptoms are minimal.